Spatial distribution of kidney disease in the contaminated site of Taranto (Italy). Issue 12 (13th October 2017) - Benedetti, Marta; De Santis, Marco; Manno, Valerio; Minerba, Sante; Mincuzzi, Antonella; Morabito, Angela; Panocchia, Nicola; Soggiu, Maria Eleonora; Tanzarella, Annalisa; Pastore, Tiziano; Bossola, Maurizio; Giua, Roberto; et al.
Abstract : Background: Exposure to heavy metals has been associated with kidney disease. We investigated the spatial distribution of kidney disease in the industrially contaminated site of Taranto. Methods: Cases were subjects with a first hospital discharge diagnosis of kidney disease. Cases affected by specific comorbidities were excluded. Standardized Hospitalization Ratios (SHRs) were computed for low/high exposure area and for modeled spatial distribution of cadmium and fine particulate matter. Result: Using the high/low exposure approach, in subjects aged 20‐59 years residing in the high exposure area a significant excess of hospitalization was observed in males and a non‐significant excess in females. No excesses were observed in subjects aged 60 years and over. The analysis by the modeling approach did not show a significant association with the greatest pollution impact area. Conclusion: Due to the excesses of hospitalization observed in the high/low exposure approach, a continuing epidemiological surveillance of residents and occupational groups is warranted.